Pengaruh Desain Produk, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Batik Pada CV. Wecono Asri Kediri - Syelfanda Putrifasari; Miftahul Munir; Agung Pambudi Mahaputra (Journal of Creative Student Research, 2023)
This research aims to test and explain the influence of product design, product quality and price on batik purchasing decisions at CV. Wecono Asri Kediri partially and simultaneously. This research uses quantitative methods and the population studied is all consumers who have purchased batik in the last 3 months. The number of samples taken was 91 respondents, and the sampling method used was non-probability sampling with accidental sampling. Data was collected through questionnaires. The research results show that (1) product design has a positive and significant effect on purchasing decisions with a t value of 3.724 and a sig value. 0.000 < 0.05; (2) product quality has a positive and significant effect on purchasing decisions with a t value of 2.517 and a sig value. 0.014 < 0.05; (3) price has a positive and significant effect on purchasing decisions with a t value of 3.696 and a sig value. 0.000 < 0.05; (4) product design, product quality and price together have a positive and significant effect on purchasing decisions with an F value of 57.153 and a sig value. 0.000 < 0.05. Decision to purchase batik at CV. Wecono Asri is influenced by these three variables by 66.3%, while the rest is influenced by other factors not examined in this research.